Roll a D6: a role-playing game based approach to the EFL classroom - da Rocha, Fabian Quevedo (BELT - Brazilian English Language Teaching Journal, 2019)
This article describes the benefits of using Role-playing games (RPGs) in EFL learning contexts. It is divided in three main parts: the first part introduces the concept and origins of RPGs and briefly discusses their communicative and collaborative aspects; the second part approaches the RPG systematic to the concepts of communicative language teaching (CLT), task based learning (TBL), and active learning as a means to demonstrate how EFL learners can benefit from an approach that involves RPGs; the third part describes and discusses the learning outcomes of a set of RPG based tasks that were developed and used in an EFL context with a group of nine teenagers aging from 12 to 17 years old during their fourth semester in a language school. The article closes with considerations on how RPG based learning can help learners develop not only their speaking and interpersonal skills, but also autonomy.